Supracardiac Total Anomalous Pulmonary Venous Connection (KYAMC Journal, 2019)
Total anomalous pulmonary venous connection (TAPVC) is a rare congenital heart disease in which there is developmental absence of connection of all four pulmonary veins with the left atrium. To report a rare case and share our experience in surgery and post-operative management for supracardiac TAPVC. Patient with supracardiac TAPVC with atrial septal defect (ASD) secundum variety with rudimentary patent ductus arteriosus (PDA) underwent rechanneling of pulmonary veins to left atrium (LA) with gluteryldehye treated autologous pericardial patch closure of ASD with ligation of ascending vertical vein and ligation of rudimentary PDA.Post operatively there were no events of pulmonary hypertensive crisis, low cardiac output syndrome, right heart failure or conduction defect were observed and echocardiogram showed adequate pulmonary venous drainage with no residual shunt across the interatrial septum. Marked development in surgical results of TAPVC has been observed in recent years with declining mortality rate from 65% in early sixties to 5% in current surgical scenerio.KYAMC Journal Vol. 10, No.-2, July 2019, Page 118-121